Crisis management and warning procedures - Valérie November; Reynald Delaloye; Marion Penelas (Revue de Géographie Alpine)
Based on two flood events that recently affected new housing areas in very different political, organisational and hydrological contexts, this article examines the practices of actors involved in emergency and crisis situations in Switzerland. In both cases, the actors are identified – through their role and their position in the various procedures related to crisis management – and an inventory is made of the documents used. The study examines how the flood events were managed, identifies the organisational changes that followed the crises, and determines how the risk was conceived and to what extent it was formalised by the different actors both before and after the floods. Finally new forecasting and warning procedures that were set up following the events are described. The study shows that floods have a decisive impact on the production of knowledge, but that this phenomenon varies according to the actors. Events such as floods also sometimes reveal the existence of "latent" knowledge, or knowledge that is available but has not yet been integrated into institutional procedures. In terms of both forecasting and crisis management, these events also provide the opportunity to test information channels and to identify and correct any problems relating to organisation, cooperation or the reliability of means of communication. Among other things, the risks and crises related to flooding modify the dynamics and policies of the local area as a result of readjustments in the networks of actors. The introduction of emergency and crisis management measures appears more effective, however, than the reorganisation of planning and development procedures, a process which generally takes a lot longer. Nevertheless, since the recollection of events tends to fade with time, it is important that risks find a more concrete form of spatial expression on the landscape.